2021
DOI: 10.1016/j.annemergmed.2020.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Giant inverted T waves in a patient with COVID-19 infection

Abstract: . The differential diagnosis of giant inverted T waves in the ECG includes, among others, Takotsubo syndrome (TTS). In a critically ill patient with acute hemodynamic or respiratory deterioration, a stress-related cardiomyopathy syndrome needs to be ruled out. In COVID-19 infection the main physiopathological mechanisms include systemic inflammatory response syndrome and thrombosis, which can condition cardiovascular complications. We present the case of a patient with COVID-19 infection who develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Reviews, opinion articles, studies that diagnosed COVID-19 without confirmatory PCR testing, a case with significant coronary artery disease, and irrelevant topics were excluded. 40 articles with 52 cases were included in our review [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Reviews, opinion articles, studies that diagnosed COVID-19 without confirmatory PCR testing, a case with significant coronary artery disease, and irrelevant topics were excluded. 40 articles with 52 cases were included in our review [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… 190 Takotsubo cardiomyopathy is a non-ischemic cardiomyopathy characterized by transient weakening of the cardiomyocytes and subsequent ballooning of the apex. 191 , 192 In all, 2–7.75% of COVID-19 patients presenting with acute coronary syndrome were diagnosed with stress-induced cardiomyopathy. Nearly one-third of the COVID-19 patients with myocardial involvement were complicated by cardiogenic shock.…”
Section: Extrapulmonary Complicationsmentioning
confidence: 99%
“… 195 In all, 16.7% of patients hospitalized with COVID-19 and 44% of those referred to ICU developed cardiac arrhythmia. 192 , 196 , 197 Abnormal PR interval behavior with increasing heart rate and QT prolongation are frequently observed in critically ill patients. 196 , 198 it remains unclear whether high prevalence of heart failure in patients hospitalized with COVID-19 with a known history of cardiac disease, results from worsening of preexisting left ventricular dysfunction or newly developed cardiomyopathy.…”
Section: Extrapulmonary Complicationsmentioning
confidence: 99%
“…[ 4 ] A recent study showed that elevation of proinflammatory molecules, such as high-sensitivity C-reactive protein and IL-6, as well as markers of myocardial damage such as hs-cTnI and NT-proBNP, were associated with an increase in in-hospital mortality in all severe cases. [ 5 ] However, increased cardiac indicators had more important values than inflammatory factors in the prognostic assessment of patients with COVID-19,[ 4 ] which may possibly indicate direct myocardial affection by the viral infection other than the damage suffered by the myocardium due to systemic vascular and coronary involvement.…”
Section: Discussionmentioning
confidence: 99%